Family Communication Patterns in Javanese Culture and Their Influence on Children's Emotional Development: A Qualitative Study - Kalfin, Kalfin; Azahra, Astrid Sulistya; Yuningsih, Siti Hadiaty (Communication In Research And Publications, 2024)
This research examines the application of communication patterns in Javanese cultural families and their impact on children's emotional development. Qualitative descriptive methods were used with in-depth analysis of field data. Data was obtained from interviews and observations of 18 families with socio-economic variations. The results show that family communication patterns play a central role in shaping children's emotional development. Authoritarian, permissive, and authoritative/democratic communication patterns were identified as the main patterns. Implementing democratic communication patterns has a positive impact on children's emotional development. Family understanding regarding the relationship between family communication and children's emotional development needs to be improved. The combination of Javanese and modern cultural values and religious life plays an important role in supporting children's emotional development. This research provides an in-depth view of communication patterns and their influence on children's emotional development in the context of Javanese culture. It is hoped that the implications of these findings will help families strengthen positive relationships and support children's emotional well-being in a rich and diverse cultural context. By understanding more deeply about communication patterns in Javanese families and their impact on children's emotional development, it is hoped that this research can provide practical guidance for families in strengthening positive relationships and supporting children's emotional well-being in the unique Javanese cultural context.